DEVELOPMENT OF CREATIVE ABILITY OF STUDENTS IN PRIMARY EDUCATION AS A PEDAGOGICAL PROBLEM - Orolboy Kulmominov; Feruza Ibragimova (Scholar Express Journal, 2024)
This article describes the methods of developing students' creative abilities in primary grades, and discusses the general characteristics of creativity and its advantages.
Keywords: Primary education; lesson; method; integration